Mycobacterium genavense splenitis in a pet rabbit (Oryctolagus cuniculus) presented for fracture - Paoletti, C; Rosas-Navarro, J.; Godart, PO; Quinton, JF (Journal of the Hellenic Veterinary Medical Society, 2023)
Mycobacteriosis is an uncommon infection that has been sporadically described among wild, farmed and pet rabbits. To date, only one case of Mycobacterium genavense infection has been reported in a dwarf rabbit presenting with granulomatous pneumonia. This new case report describes granulomatous splenitis caused by M. genavense in a pet rabbit brought in for lameness caused by a femoral fracture. The initial blood test, X-ray, abdominal ultrasound, and bone marrow and spleen cytology results were consistent with a diagnosis of a metastatic giant-cell tumour. The rabbit underwent successful femoral osteosynthesis, and six months later, following the occurrence of a second spontaneous fracture and a worsening of overall health, the patient was euthanised. The postmortem histological examination showed severe granulomatous splenitis caused by acid-fast bacilli identified as M. genavense by real-time PCR analysis. The route of infection remains unknown, yet the lack of pulmonary involvement likely rules out airborne transmission. M. genavense infection, although rarely described in pet rabbits, appears to be an emerging pathogen and should be included among the differential diagnoses for pneumonia and splenomegaly.